Treatment of AO/OTA 31-A3 intertrochanteric femoral fractures with a percutaneous compression plate (Clinics, 2014)
OBJECTIVE: AO/OTA 31-A3 intertrochanteric femoral fractures have completely different fracture line directions and biomechanical characteristics compared with other types of intertrochanteric fractures. The choice of the fixation method has been a focus of dispute among orthopedic trauma surgeons. The purpose of this study was to review the outcomes of these fractures treated with a percutaneous compression plate at our institute. METHOD: Seventeen patients with AO/OTA 31-A3 intertrochanteric femoral fractures were treated with a percutaneous compression plate at our institute from January 2010 to December 2011. The clinical data and imaging results were retrospectively analyzed. RESULTS: The medical complication of popliteal vein thrombosis occurred in one patient. Sixteen patients were followed up for 12 to 21 months. Two patients had malunion and mild pain. Fracture collapse occurred in two patients, with one having head penetration. These two patients had moderate pain. There were no occurrences of nonunion or reoperation. The mean Harris hip score obtained during the last follow-up was 84.1 (61-97). Patients with a poor quality of reduction were more likely to have pain results (p = 0.001). A trend existed toward the presence of a poor quality of reduction (p = 0.05) in patients with a collapse of fracture. Patients with poor preoperative mobility were more likely to have a lower Harris hip score (p = 0.000). CONCLUSION: The percutaneous compression plate is an alternative device for the treatment of AO/OTA 31-A3 intertrochanteric femoral fractures. Good fracture reduction and an ideal placement position of the neck screw are important in the success of the device.